Thermochemical conversion of different biomass feedstocks into hydrogen for power plant electricity generation. (15th May 2023) - Pocha, Chaitanya Kumar Reddy; Chia, Wen Yi; Silvanir; Kurniawan, Tonni Agustiono; Khoo, Kuan Shiong; Chew, Kit Wayne
Graphical abstract: Highlights: Biohydrogen is an attractive renewable energy source of clean energy. Microwave plasma techniques offer high reaction temperature and energy density. Biomass gasification has the lowest GHG emission over other production routes. Conversion technologies of hydrogen to electricity are reviewed. Korea operates the world's largest hydrogen fuel cell power plant in 2021. Abstract: Most hydrogen production technologies are dependent on non-renewable resources, which are not sustainable in the long run. However, H2 can be produced in the future from renewable sources, becoming one of the cleanest energy carriers. Compared to other biomass treatment methods, the thermochemical pathways from biomass for sustainable H2 generation offers a considerable promise for its industrial use. The most studied routes are biomass gasification and reformation of the bio-oil generated by biomass pyrolysis, while some works on supercritical water gasification and bio-oil gasification are extensively developed to improve hydorgen production efficiency. This review discusses the most current developments in research on the methods of pyrolysis, gasification, steam reformation, and microwave-induced plasma for producing hydrogen from various types of biomasses, including lignocellulosic and woody biomasses. By utilizing the hydrogen produced from biomass, possibilities of creating a sustainable city were analyzed. There are many upgraded technologies to generate electricity using hydrogen produced from biomass such as gas turbines, combined cycle power plants, and fuel cells. The environmental feasibility of hydrogen usage was also evaluated, along with the status quo of hydrogen power plants in several countries. This review contributes to the large-scale implementation of hydrogen energy with in-depth discussion on the latest development.